The impact of minimum wages on employment and income inequalities – the Latin American experience - Sordyl, Marta (Wpływ płacy minimalnej na zatrudnienie i nierówności dochodu – doświadczenia krajów Ameryki Łacińskiej, 2019)
The minimum wage is one of the most basic policy tools to provide workers with an adequate income and reduce excessive income inequalities. Traditional models of the labour market predict, however, that setting the minimum wage above the market-clearing level will lead to lower employment, especially for the least efficient workers. Recent experience in Latin American countries is in this context quite confusing – in some of them the minimum wage rose significantly, reducing wage disproportions, but at the same time employment increased and the informal sector shrank considerably. The trends were not stable, with a marked reversal visible in the last few years. The aim of the paper is to identify mechanisms through which the minimum wage affects labour market aggregates and to assess its impact on employment and income inequalities. Empirical data is analyzed for the region’s biggest economies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 101-112
Keywords: minimum wage; employment; income inequalities; płaca minimalna; zatrudnienie; nierówności dochodowe